Public Accountants: Law Enforcement of Violations of Auditing Practices - Hidayatullah; Agus Triono; FX Sumarja (Journal of Legal and Cultural Analytics, 2023)
The financial report is a product of management’s responsibility to shareholders. As a report prepared by management, an independent party must conduct an examination and provide a fair opinion on the financial report. In Indonesia, based on Law No. 5 of 2011 concerning Public Accountants, the only party authorized by the state through the Ministry of Finance to audit financial statements is a public accountant under the auspices of a public accounting firm. The audit carried out by the Public Accountant did not fully exercise its authority, as can be seen from the many scandals over the audited financial statements. For this scandal, regulations and laws have determined what sanctions can be given, both in the form of administrative sanctions and legal sanctions, both civil and civil. as well as punishment for responsible parties, including Public Accountants who provide guarantees for the fairness of the Financial Statements. Apart from that, other problems also emerged; the auditees used many fake audit reports, either those made by the auditees themselves by falsifying the names and signatures of the Public Accountants or those carried out by persons who claimed to be from a Public Accounting Firm while not a party with a Public Accountant license.